Media Komunikasi Visual Penerapan Prinsip Desain Dalam Buku Cerita Bergambar Aku Ingin Hidup Untuk Anak Sekolah Minggu Umur 7-9 Tahun - Sharon De Gracia Matingo; Ratih Pertiwi (VisArt: Jurnal Seni Rupa dan Design, 2024)
Visual Communication as a medium for applying design principles for designing the picture story book "I Want to Live" for Sunday school children aged 7-9 years. This research applies design principles in designing the picture story book "I Want to Live" for Sunday school children aged 7-9 years. This book is designed to convey a moral message in an interesting way by using colors, typography and illustrations that are appropriate to children's psychology. The research method involves analyzing children's needs, interviews with Sunday school teachers, and trials on the target audience. The results show that appropriate design can increase children's visual appeal and understanding of the message conveyed, making this book an effective and enjoyable learning medium. It is hoped that this research can be a reference for designers and educators in developing visual teaching materials for children.